Multi-Level Image of a Successful University Graduate in the Information Management for the Supply Chain in Education System - Elena B. Kmet (International Journal of Supply Chain Management, 2019)
Abstract— The paper presents the results of a study devoted to the analysis of the criteria for the success of graduates in information management of educational system for supply chain. The relevance of the study is dictated by the increased interest of universities to the success of their graduates, which is associated not only with positions in the prestigious world ranking of QS Top universities, but also with problems of managing the competitiveness of universities and communications with potential consumers of educational services. The proper supply chain in educational system needs proper information, so lack of information integration makes difficulties in high schools, universities and careers. The study used such methods of data collection as a content analysis of scientific publications, a survey of respondents, and statistical data analysis implemented in the SPSS statistical package were used as data analysis. Results: analysis of survey data allowed us to describe a multi-level image of a successful graduate, formed in the minds of respondents, in the context of personal qualities, approaches to building a career, rating of personalities of successful people, time of interest in the profession, job characteristics of a university graduate in the first year. For the first time, the work presents a comparative description of the image of a successful university graduate and a rating of successful personalities in the context of senior students 'and students' points of view. Practical significance: the results are of interest for departments and structural divisions of universities, working with high school students and their parents, in the context of building communication, building a dialogue for directional impact and developing advertising materials. The results of the study allow to determine the successful graduates based on the supply chain, information about which should be broadcast in the content of the university (on the website, in groups of social networks, Indoor- and print advertising).